Traditional Islamic Education in Kerinci: Historical Reconstruction and Adat-Islam Integration - Ravico, Ravico; Siregar, Anggi Desviana; Ramadhona, Nuzulur (Yayasan Keluarga Guru Mandiri, 2025)
This study examines the traditional Islamic education system in Kerinci, Sumatra, a region that has remained relatively overlooked in Indonesian Islamic education scholarship compared to areas such as Java, Aceh, and West Sumatra. Despite Islam's profound influence on the culture and social structure of Kerinci society, historical documentation of its educational practices remains limited. This research aims to reconstruct the history of traditional Islamic education in Kerinci during the 18th and 19th centuries, analyze its curriculum, and explore the integrative role of local customs (adat) in its development. Employing a multidisciplinary approach, this study combines historical, philological, and anthropological methods to examine the topic. Primary data were collected through the examination of Malay-Arabic manuscripts, oral traditions, and in-depth interviews with religious and customary leaders. Secondary sources include colonial archives and previous studies. The analysis follows a heuristic approach, incorporating data collection, source verification, critical interpretation, and historiographic writing. The findings reveal two main educational models: ngajai (informal community-based teaching) and ngajai di umah syiak (instruction at the homes of religious leaders), both of which integrated Quranic literacy, moral education, and local customary values. This research makes a significant contribution by providing the first comprehensive documentation of Islamic education in Kerinci and offers a methodological innovation for studying oral tradition-based Islamic education systems in local contexts.